843 QUANTIFICATION OF VENTRICULAR FUNCTIONAL MITRAL REGURGITATION USING THE VOLUMETRIC METHOD BY 3D-ECHOCARDIOGRAPHY. (15th December 2022) - Tomaselli, Michele; Curti, Emanuele; Radu, Noela; Perelli, Francesco; Cascella, Andrea; Stucchi, Davide; Pece, Cinzia; Camponetti, Virginia; Oliverio, Giorgio; Ciambellotti, Francesca; Gavazzoni, Mara; Heilbron, Francesca; et al.
Abstract: Background: ventricular functional mitral regurgitation (v-FMR) is associated with an increased risk of mortality and hospitalization for heart failure. In this setting, the echocardiographic assessment of v-FMR severity using 2D proximal isovelocity surface area (PISA) yields several limitations, potentially leading to an underestimation of v-FMR severity. An alternative approach is to derive the regurgitant volume (RegVol) and the effective regurgitant orifice area (EROA) using the three-dimensional echocardiography (3DE) to estimate left ventricular volumes (volumetric method, VM). However, a direct comparison of these methods has never been tested. Accordingly, the aims of our study are: i; to compare both 2D PISA measurements of EROA and RegVol with those obtained by VM using 3DE, ii; to test their accuracy using the 3D planimetry of vena contracta area (3D-VCA) of MR jet, as reference. Methods: we retrospectively analysed 82 (mean age 75±12, 48% men, 79% sinus rhythm, 85% with ischemic cardiomyopathy, 15% with dilated cardiomyopathy) consecutive patients with v-FMR and reduced left ventricular ejection fraction (LVEF <50%), acquired between July 2020 and October 2021. Exclusion criteria were: age < 18 years, primary MR, presence of intra-cardiac shunts, greater than mild aortic regurgitation, and inadequate acoustic window. PISA EROA was calculated using the formula: 6.28 r 2 ×Va /Vp (where: r= PISA radius, Va = aliasing velocity, Vp = MR peak velocity). FMR regurgitant volume (RegVol) by PISA was calculated as EROA×VTIMR, where VTIMR represents the time–velocity integral of the CW Doppler MR jet tracing. FMR RegVol by 3DE volumetric method (VM) was calculated as: total LV stroke volume (LV SV) – forward LV SV (Ao SV). LV SV was obtained by subtracting the respective end-systolic (ESV) from the end-diastolic (EDV) volumes measured by 3DE. Ao SV was calculated by multiplying LV outflow area by LV outflow tract velocity time integral (VTI). EROA by VM was calculated as the MR RegVol divided by VTIMR. In a group of 10 patients, the quantification of 3D-VCA was performed by multiplanar reconstruction using a dedicated software package (EchoPAC 204 GE Vingmed, Horten, Norway). Results: average LV end-diastolic and end-systolic volumes, total stroke volume, LVEF and global longitudinal strain were 211±25 mL, 134±17 mL, 73±9 mL, 36±8% and, 9.4±2.7% respectively. Median Ao SV was 50±12 mL. Left atrial volume and left atrial reservoir strain were respectively 99±19 mL and 10±16%. Both EROA and RegVol by VM were larger than EROA (0.17± 0.09 cm2 vs 0.11± 0.01 cm2; p<0.001) and RegVol (25.7±12.1 mL vs 17.2±9.9 mL; p<0.001) by PISA, respectively. Compared to 3D-VCA, EROA by VM resulted more accurate than EROA by PISA (bias= -0.15 cm 2, LOA ±0.24 cm 2 vs bias= -0.25 cm 2, LOA ±0.29 cm 2 ). Finally, VM EROA (r= 0.778) showed a better correlation than PISA EROA (r= 0.681) with the 3D-VCA (p<0.001). Conclusions: in patients with v-FMR, the echocardiographic assessment of EROA and RegVol using the 3DE volumetric method showed larger values compared to the conventional PISA method, and a closer correlation with the 3D VCA. Accordingly, the 3DE VM could improve the accuracy of evaluation of v-FMR severity. Larger studies with longer clinical follow-up are needed to define if it translates into improved risk stratification and may address patients' management.